Neodymium-iron-boron magnet and method for producing same
Patent Information
- Application Number
- CN202210475086.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-04-29
AI Technical Summary
[0004]本发明为了解决现有技术中制备耐热性好的钕铁硼磁体时,成本较高或者剩磁下降的问题,而提供了一种钕铁硼磁体及其制备方法
[0090] The neodymium iron boron magnets described in this invention possess high remanence and coercivity, with a room-temperature remanence (Br) exceeding 13.18 kGs and a room-temperature coercivity (Hcj) exceeding 21.8 kOe. Furthermore, the neodymium iron boron magnets of this invention exhibit good heat resistance, with a Br temperature coefficient (|α|) below 0.10% at 150℃ and a Hcj temperature coefficient (|β|) not exceeding 0.45% at 150℃.
Smart Images

Figure CN117012485B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a neodymium iron boron magnet and its preparation method. Background Technology
[0002] RTB-based rare-earth permanent magnet materials are widely used in hard drive drives, electric vehicle drive motors, wind power generators, and home appliances. With the miniaturization of motors and the increased heat generation due to high current densities, the heat resistance requirements for the rare-earth permanent magnets used are further increasing. Maintaining the coercivity of the magnet at high temperatures has become one of the important research topics in this field. Existing technologies typically improve heat resistance by adding heavy rare-earth elements to increase coercivity, but heavy rare-earth elements are expensive and scarce. Another promising technological direction is grain refinement. Refining the grain size from 1 μm to the nm level can improve the coercivity and heat resistance of the magnet. However, after refining to the nm level, the grains tend to be isotropic, and the remanent magnetization decreases, making it impossible to provide sufficient magnetic flux for motor applications.
[0003] To address the above problems, this invention provides a rare-earth permanent magnet material that also possesses a good coercivity temperature coefficient and remanent magnetization. Summary of the Invention
[0004] This invention addresses the problems of high cost or decreased remanence in the preparation of heat-resistant NdFeB magnets in existing technologies by providing a NdFeB magnet and its preparation method. The NdFeB magnet of this invention exhibits good heat resistance and high remanence.
[0005] The present invention solves the above-mentioned technical problems through the following technical solutions.
[0006] This invention provides a neodymium iron boron magnet, which comprises the following components:
[0007] Nd: 20.0%–30.0%;
[0008] R': 0 to 10.0%, and not 0; R' is one or more of Pr, Dy, and Tb;
[0009] Co: 1.0%–5.0%;
[0010] M: 0.1% to 1.2%; M is one or more of Al, Cu and Ga, and M includes at least Ga;
[0011] The content of B is 0.8% to 0.96%;
[0012] The balance is Fe;
[0013] The percentages represent the percentage of each component by mass in the neodymium iron boron magnet.
[0014] The neodymium iron boron magnet includes a first structure, a second structure, and a third structure; the first structure includes Nd2Fe 14 B is the main phase and its grain boundary phase; the second structure includes R'2Fe. 14 B main phase and its grain boundary phase; the third structure is the boundary between the first structure and the second structure; the content of the M element in the third structure is lower than its content in the first structure or the second structure; the Nd2Fe 14 B main phase and the R'2Fe 14 The B main phase exhibits nanoscale elongated shapes.
[0015] In this invention, the grain boundary phase refers to the phase located between two adjacent main phase grains, such as Nd2Fe. 14 B main phase and Nd2Fe 14 The phases between the main phase B, or R'2Fe 14 B main phase and R'2Fe 14 Phases between the main phase B.
[0016] In this invention, preferably, the first structure accounts for 45.0% to 70.0% of the volume of the neodymium iron boron magnet, for example, 58.0%, 62.0% or 68.0%.
[0017] In this invention, preferably, the second structure accounts for 25.0% to 50.0% of the volume percentage of the neodymium iron boron magnet, for example, 25.0%, 26.0%, 30.0% or 37.0%.
[0018] In this invention, preferably, the third structure accounts for 5.0% to 10.0% of the volume percentage of the neodymium iron boron magnet, for example, 6.0% or 8.0%.
[0019] In a preferred embodiment of the present invention, the neodymium iron boron magnet comprises 58.0% of a first structure, 37.0% of a second structure, and 5.0% of a third structure, the percentages being the volume percentages of the neodymium iron boron magnet.
[0020] In a preferred embodiment of the present invention, the neodymium iron boron magnet comprises 70.0% of a first structure, 25.0% of a second structure, and 5.0% of a third structure, the percentages being the volume percentage of the neodymium iron boron magnet.
[0021] In a preferred embodiment of the present invention, the neodymium iron boron magnet comprises 68.0% of a first structure, 26.0% of a second structure, and 6.0% of a third structure, the percentages being the volume percentage of the neodymium iron boron magnet.
[0022] In a preferred embodiment of the present invention, the neodymium iron boron magnet comprises 62.0% of a first structure, 30.0% of a second structure, and 8.0% of a third structure, the percentages being the volume percentage of the neodymium iron boron magnet.
[0023] In this invention, nanoscale elongated shape refers to a shape in which the width of the grain is less than 1000 nm.
[0024] In this invention, preferably, the Nd2Fe 14 The grain width of the B main phase is less than 800 nm, more preferably less than 500 nm, and even more preferably less than 200 nm, for example 43.7 nm, 75.5 nm, 115.0 nm or 151.0 nm.
[0025] In this invention, preferably, the R'2Fe 14 The grain width of the B main phase is less than 800 nm, more preferably less than 500 nm, and even more preferably less than 200 nm, for example 43.7 nm, 75.5 nm, 115.0 nm or 151.0 nm.
[0026] In this invention, the Nd content is preferably 20.0% to 26.0%, for example 20.65%, 24.0%, 24.8% or 25.5%.
[0027] In this invention, preferably, R' is Pr, and the content of Pr is preferably 7.0% to 10.0%, for example 7.15% or 9.59%.
[0028] In this invention, preferably, R' is Pr and Dy, wherein the content of Pr is preferably 3.0% to 7.0%, for example 3.36% or 6.49%; and the content of Dy is preferably 2.0% to 4.0%, for example 2.92% or 3.08%.
[0029] In this invention, the content of Co is preferably 1.5% to 3.5%, for example 1.7%, 2.4%, 3.0% or 3.5%.
[0030] In this invention, preferably, M is Ga, and the content of Ga is preferably 0.1% to 0.2%, for example 0.18%.
[0031] In this invention, preferably, M is Ga and Cu, wherein the content of Ga is preferably 0.4% to 0.5%, for example 0.43%; and the content of Cu is preferably 0.6% to 0.7%, for example 0.64%.
[0032] In this invention, preferably, M is Ga and Al, wherein the content of Ga is preferably 0.2% to 0.35%, for example 0.23% or 0.32%; and the content of Al is preferably 0.01% to 0.1%, for example 0.07% or 0.08%.
[0033] In this invention, the content of B is preferably 0.85% to 0.92%, for example 0.85%, 0.89%, 0.9% or 0.92%.
[0034] In this invention, the phrase "the balance is Fe" does not preclude the presence of other elements besides those mentioned in this invention in the NdFeB magnet. When the NdFeB magnet contains other elements besides those mentioned in this invention, the amount of Fe is adjusted accordingly so that the mass percentage of elements other than Fe in the NdFeB magnet is within the range defined by this invention.
[0035] In this invention, the Fe content is preferably 62.0% to 66.0%, for example 62.39%, 64.37%, 64.44% or 65.16%.
[0036] In one specific embodiment of the present invention, the neodymium iron boron magnet comprises the following components: Nd 20.65%, Pr 9.59%, Co 3.50%, Ga 0.18%, B 0.92%, and Fe 65.16%.
[0037] In one specific embodiment of the present invention, the neodymium iron boron magnet comprises the following components: Nd 25.5%, Pr 3.36%, Dy 3.08%, Co 1.70%, Ga 0.43%, Cu 0.64%, B 0.85%, and Fe 64.44%.
[0038] In one specific embodiment of the present invention, the neodymium iron boron magnet comprises the following components: Nd 24.8%, Pr 7.15%, Co 2.4%, Ga 0.32%, Al 0.07%, B 0.89%, and Fe 64.37%.
[0039] In one specific embodiment of the present invention, the neodymium iron boron magnet comprises the following components: Nd 24.0%, Pr 6.49%, Dy 2.92%, Co 3.0%, Ga 0.23%, Al 0.08%, B 0.9% and Fe 62.39%.
[0040] This invention provides a method for preparing a neodymium iron boron magnet as described above, comprising the following steps:
[0041] S1. First, second, and third thin strips are prepared respectively; wherein...
[0042] The first thin strip is obtained by melting and rapidly quenching the raw material of the first thin strip; the raw material of the first thin strip includes Nd 29.5% to 32.0%, Co 1.0% to 5.0%, M 0.05% to 0.2%, B 0.86% to 0.96%, and the balance is Fe; wherein M is one or more of Al, Cu and Ga, and M includes at least Ga; the percentage is the mass percentage of the raw material of the first thin strip;
[0043] The second strip is obtained by melting and rapidly quenching the raw material of the second strip; the raw material of the second strip includes R' 27.0% to 30.0%, B 0.86% to 0.96%, and the balance being Fe; wherein, R' is one or more of Pr, Dy and Tb; the percentage is the mass percentage of the raw material of the second strip;
[0044] The third thin strip is obtained by melting and rapid quenching the raw material of the third thin strip; the raw material of the third thin strip includes R' 80.0% to 97.5% and M 2.5% to 18%; wherein, R' is one or more of Pr, Dy and Tb; M is one or more of Al, Cu and Ga; the percentage is the mass percentage of the raw material of the third thin strip;
[0045] S2. The powder mixture is then subjected to hot pressing and hot deformation in sequence;
[0046] The powder mixture comprises 70.0% to 90.0% of the powder of the first thin strip, 9.0% to 30.0% of the powder of the second thin strip, and 0.5% to 5.0% of the powder of the third thin strip; the percentages are the mass percentages of the powder mixture.
[0047] In this invention, in step S1, the content of Ga in the raw material of the first thin strip is preferably 0.1% to 0.6%, for example 0.3%, 0.4% or 0.5%.
[0048] In a specific embodiment of the present invention, in step S1, the raw materials of the first thin strip include 29.5% Nd, 5.0% Co, 0.1% Ga, 0.96% B, and 64.44% Fe; the percentages are the mass percentages of the raw materials of the first thin strip.
[0049] In a specific embodiment of the present invention, in step S1, the raw materials of the first thin strip include 30.0% Nd, 2.0% Co, 0.5% Ga, 0.88% B, and 66.62% Fe; the percentages are the mass percentages of the raw materials of the first thin strip.
[0050] In a specific embodiment of the present invention, in step S1, the raw materials of the first thin strip include 31.0% Nd, 3.0% Co, 0.4% Ga, 0.9% B, and 64.7% Fe; the percentages are the mass percentages of the raw materials of the first thin strip.
[0051] In a specific embodiment of the present invention, in step S1, the raw materials of the first thin strip include 32.0% Nd, 5.04% Co, 0.3% Ga, 0.92% B, and 62.78% Fe; the percentages are the mass percentages of the raw materials of the first thin strip.
[0052] In this invention, in step S1, preferably, in the raw material of the second thin strip, R' is Pr, and the content of Pr is preferably 29.0%, 29.5%, or 30.0%.
[0053] In this invention, in step S1, preferably, in the raw material of the second thin strip, R' is Dy, and the content of Dy is preferably 28.0%.
[0054] In a specific embodiment of the present invention, in step S1, the raw material of the second thin strip includes 30.0% Pr, 0.86% B, and 69.14% Fe; the percentages are the mass percentages of the raw material of the second thin strip.
[0055] In a specific embodiment of the present invention, in step S1, the raw material of the second thin strip includes 28.0% Dy, 0.96% B, and 71.04% Fe; the percentages are the mass percentages of the raw material of the second thin strip.
[0056] In a specific embodiment of the present invention, in step S1, the raw material of the second thin strip includes 29.0% Pr, 0.94% B, and 70.06% Fe; the percentages are the mass percentages of the raw material of the second thin strip.
[0057] In a specific embodiment of the present invention, in step S1, the raw material of the second thin strip includes 29.5% Pr, 0.94% B, and 69.56% Fe; the percentages are the mass percentages of the raw material of the second thin strip.
[0058] In this invention, in step S1, preferably, the raw material of the second thin strip further includes Co, and the content of Co is preferably 1.0% to 5.0%, which is the mass percentage of the raw material of the second thin strip.
[0059] In this invention, in step S1, preferably, in the raw material of the third thin strip, R' is Pr, and the content of Pr is preferably 89.0%, 84.0%, or 96.5%.
[0060] In this invention, in step S1, preferably, in the raw material of the third thin strip, R' is Dy, and the content of Dy is preferably 97.2%.
[0061] In this invention, in step S1, preferably, in the raw material of the third thin strip, M is Ga, and the content of Ga is 4.0% to 12.0%, for example 11.0%.
[0062] In this invention, in step S1, preferably, in the raw material of the third thin strip, M is Cu, and the content of Cu is 14.0% to 17.0%, for example 16.0%.
[0063] In this invention, in step S1, preferably, in the raw material of the third thin strip, M is Al, and the content of Al is 2.5% to 3.5%, for example 2.8%.
[0064] In a specific embodiment of the present invention, in step S1, the raw material of the third thin strip includes 89.0% Pr and 11.0% Ga; the percentage is the mass percentage of the raw material of the third thin strip.
[0065] In a specific embodiment of the present invention, in step S1, the raw material of the third thin strip includes 84.0% Pr and 16.0% Cu; the percentage is the mass percentage of the raw material of the third thin strip.
[0066] In a specific embodiment of the present invention, in step S1, the raw material of the third thin strip includes 96.5% Pr and 3.5% Al; the percentage is the mass percentage of the raw material of the third thin strip.
[0067] In a specific embodiment of the present invention, in step S1, the raw material of the third thin strip includes 97.2% Dy and 2.8% Al; the percentage is the mass percentage of the raw material of the third thin strip.
[0068] In this invention, step S1, the smelting can be carried out using conventional methods in the art, preferably including: repeated smelting in an electric arc furnace under an inert gas protective atmosphere. The purpose of the smelting is to fully alloy the raw materials to obtain an alloy ingot.
[0069] In this invention, in step S1, the rapid quenching can be performed using conventional methods in the art, preferably including: rapid quenching in a vacuum rapid quenching furnace under an inert gas protective atmosphere, wherein the rotational speed of the cooling roller is 25 m / s. Preferably, the inert gas is Ar.
[0070] In this invention, in step S2, preferably, the powder mixture comprises 70.0% of the powder of the first thin strip, 29.0% of the powder of the second thin strip, and 1.0% of the powder of the third thin strip; the percentages are the mass percentages of the powder mixture.
[0071] In this invention, in step S2, preferably, the powder mixture comprises 85.0% of the powder of the first thin strip, 11.0% of the powder of the second thin strip, and 4.0% of the powder of the third thin strip; the percentages are the mass percentages of the powder mixture.
[0072] In this invention, in step S2, preferably, the powder mixture comprises 80.0% of the powder of the first thin strip, 18.0% of the powder of the second thin strip, and 2.0% of the powder of the third thin strip; the percentages are the mass percentages of the powder mixture.
[0073] In this invention, in step S2, preferably, the powder mixture comprises 75.0% of the powder of the first thin strip, 22.0% of the powder of the second thin strip, and 3.0% of the powder of the third thin strip; the percentages are the mass percentages of the powder mixture.
[0074] In this invention, in step S2, the powder of the first thin strip, the powder of the second thin strip, and the powder of the third thin strip can be obtained by crushing the first thin strip, the second thin strip, and the third thin strip using conventional crushing methods in the art, and the crushing can be carried out using a crusher.
[0075] In this invention, in step S2, preferably, the method for preparing the powder mixture includes: pulverizing the first thin strip, the second thin strip, and the third thin strip respectively to obtain powder of the first thin strip, powder of the second thin strip, and powder of the third thin strip; and then mixing the powder of the first thin strip, the powder of the second thin strip, and the powder of the third thin strip.
[0076] In this invention, in step S2, preferably, the method for preparing the powder mixture includes: pulverizing the first thin strip, the second thin strip, and the third thin strip together to obtain the powder mixture.
[0077] In this invention, in step S2, preferably, the particle size D50 of the powder of the first thin strip, the powder of the second thin strip, and the powder of the third thin strip are each independently 150-250 μm.
[0078] In this invention, the purpose of hot pressing in step S2 is to obtain a densified isotropic neodymium iron boron magnet material.
[0079] In this invention, in step S2, the temperature of the hot pressing is preferably 500-650°C.
[0080] In this invention, in step S2, the hot pressing time is preferably 1 to 5 minutes, for example 2 minutes.
[0081] In this invention, in step S2, the pressure of the hot pressing is preferably 50 to 200 MPa, for example 150 MPa.
[0082] In this invention, the purpose of the thermal deformation in step S2 is to obtain anisotropic neodymium iron boron magnet material.
[0083] In this invention, in step S2, the temperature of the heat deformation is preferably 750-900°C, for example 840°C.
[0084] In this invention, in step S2, the time for thermal deformation is preferably 1 to 5 minutes, for example, 3 minutes.
[0085] In this invention, in step S2, the pressure of the thermal deformation is preferably 100-300 MPa, for example 270 MPa.
[0086] In this invention, in step S2, the deformation rate of the thermal deformation is preferably 50% to 90%, for example 70%.
[0087] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.
[0088] The reagents and raw materials used in this invention are all commercially available.
[0089] The positive and progressive effects of this invention are as follows:
[0090] The neodymium iron boron magnets described in this invention possess high remanence and coercivity, with a room-temperature remanence (Br) exceeding 13.18 kGs and a room-temperature coercivity (Hcj) exceeding 21.8 kOe. Furthermore, the neodymium iron boron magnets of this invention exhibit good heat resistance, with a Br temperature coefficient (|α|) below 0.10% at 150℃ and a Hcj temperature coefficient (|β|) not exceeding 0.45% at 150℃. Attached Figure Description
[0091] Figure 1 The image shows the EPMA diagram of the neodymium iron boron magnet in Example 1 (structure A is the first structure, structure B is the second structure, and structure C is the third structure).
[0092] Figure 2 This is a SEM image of the neodymium iron boron magnet from Example 1. Detailed Implementation
[0093] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0094] Examples 1-4
[0095] The preparation method of neodymium iron boron magnets is as follows:
[0096] (1) Smelting: The three types of thin strips were proportioned according to the composition formula in Table 1. The prepared raw materials were put into an electric arc melting furnace and repeatedly smelted in an inert gas protective atmosphere to fully alloy the ingots. After cooling, alloy ingots were obtained respectively.
[0097] (2) Rapid quenching: The alloy ingot is placed in a vacuum rapid quenching furnace and subjected to rapid quenching in an Ar protective atmosphere. The rotation speed of the cooling roller is 25 m / s, thus obtaining the first, second and third thin strips.
[0098] (3) Powdering and mixing: The first, second and third thin strips are mechanically crushed and ground and then screened to obtain powder with a size of 150-250μm; the three powders are mixed evenly using a mixer according to the mixing ratio in Table 1 to obtain a powder mixture.
[0099] (4) Hot pressing: The powder mixture is loaded into a mold and kept at 150MPa and 650℃ for 2 minutes to obtain an isotropic neodymium iron boron magnet with diameters of 15mm and 17mm.
[0100] (5) Thermal deformation: The above isotropic magnets were kept at 840℃ and 270MPa for 3 minutes to obtain an anisotropic neodymium iron boron magnet with a deformation rate of 70% and a size of Φ24mm×5mm.
[0101] Comparative Example 1
[0102] According to the final composition of Example 1, there is only one type of thin strip, which is prepared according to the above steps (1) to (5).
[0103] Comparative Example 2
[0104] The final composition is the same as in Example 1, but only two types of thin strips are prepared according to the above steps (1) to (5).
[0105] Comparative Example 3
[0106] The final composition is the same as in Example 1, but only two types of thin strips are prepared according to the above steps (1) to (5).
[0107] Comparative Example 4
[0108] Three types of thin strips were used, but the mixing ratio was not within the scope of this application, and the final composition was not within the scope of this application. The preparation was carried out according to the above steps (1) to (5).
[0109] Table 1. Component formulation of NdFeB magnets
[0110]
[0111]
[0112] The " / " indicates that the component is not present.
[0113] Effect Example
[0114] (1) FE-EPMA test
[0115] The NdFeB magnet prepared in Example 1 was polished, and its cross-section was analyzed using FE-EPMA (JEOL8530F). The results are as follows. Figure 1 As shown. From Figure 1 It can be seen that the NdFeB magnet includes three structures: structure A is the first structure, structure B is the second structure, and structure C is the third structure, with the third structure being the junction of the first and second structures. Furthermore, the volume ratios of the three structures in the NdFeB magnets prepared in Examples 1-4 are shown in Table 2.
[0116] (2) Scanning electron microscopy (SEM) test
[0117] The neodymium iron boron magnet prepared in Example 1 was used to observe the morphology and structure of the magnet material using SEM. The results are as follows: Figure 2 As shown. By Figure 2 It is known that the main phase grains in this neodymium iron boron magnet are nano-sized elongated strips with a grain width of less than 200 nm, such as 43.7 nm, 75.5 nm, 115.0 nm or 151.0 nm.
[0118] (3) Magnetic property test
[0119] The neodymium iron boron magnets prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to magnetic performance testing using the NIM-10000 bulk rare earth permanent magnet non-destructive testing system of the National Institute of Metrology of China. The results are shown in Table 2.
[0120] Table 2 Magnetic Properties of Neodymium Iron Boron Magnets
[0121]
[0122]
[0123] The data in Table 2 are explained as follows:
[0124] ①20℃Br: refers to the remanence Br of a neodymium iron boron magnet at room temperature (20℃).
[0125] ②20℃Hcj: refers to the coercivity Hcj of neodymium iron boron magnets at room temperature (20℃).
[0126] ③ Absolute value of Br temperature coefficient |α| (%): This refers to the temperature coefficient calculated based on the remanence of Br in NdFeB magnet materials at room temperature (20℃) and high temperature (150℃). The calculation formula is as follows:
[0127] Br temperature coefficient
[0128] ④ Absolute value of temperature coefficient Hcj |β| (%): This refers to the temperature coefficient calculated based on the coercivity Hcj of neodymium iron boron magnet materials at room temperature (20℃) and high temperature (150℃). The calculation formula is as follows:
[0129] Hcj temperature coefficient
[0130] As shown in Table 2, the room-temperature remanence (Br) of the NdFeB magnets prepared in the embodiments of the present invention is above 13.18 kGs, and the room-temperature coercivity (Hcj) is above 21.8 kOe, both higher than that of the comparative examples. Furthermore, the Br temperature coefficient (|α|) at 150℃ of the NdFeB magnets prepared in the embodiments of the present invention is 0.09%, lower than that of the comparative examples; the Hcj temperature coefficient (|β|) at 150℃ of the NdFeB magnets prepared in the embodiments of the present invention does not exceed 0.45%, while that of the comparative examples is above 0.47%. Therefore, the NdFeB magnets of the present invention exhibit good heat resistance.
Claims
1. A neodymium iron boron magnet, comprising the following components: Nd: 20.0%~30.0%; R': 0~10.0%, and not 0; R' is one or more of Pr, Dy and Tb; Co: 1.0%~5.0%; M: 0.1%~1.2%; M is one or more of Al, Cu and Ga, and M includes at least Ga; The content of B is 0.8%~0.96%; The balance is Fe; The percentages represent the mass percentage of each component in the neodymium iron boron magnet. The neodymium iron boron magnet includes a first structure, a second structure, and a third structure; the first structure includes Nd2Fe 14 B is the main phase and its grain boundary phase; the second structure includes R'2Fe. 14 B main phase and its grain boundary phase; the third structure is the boundary between the first structure and the second structure; the content of the M element in the third structure is lower than its content in the first structure or the second structure; the Nd2Fe 14 B main phase and the R'2Fe 14 The B main phase exhibits nanoscale elongated shapes.
2. The neodymium iron boron magnet as described in claim 1, characterized in that, The first structure accounts for 45.0% to 70.0% of the volume of the neodymium iron boron magnet; And / or, the second structure accounts for 25.0% to 50.0% of the volume of the neodymium iron boron magnet; And / or, the third structure accounts for 5.0% to 10.0% of the volume of the neodymium iron boron magnet; And / or, the Nd2Fe 14 The grain width of the B main phase is less than 800 nm; And / or, the R'2Fe 14 The grain width of the B main phase is less than 800 nm.
3. The neodymium iron boron magnet as described in claim 2, characterized in that, The first structure accounts for 58.0%, 62.0%, or 68.0% of the volume of the neodymium iron boron magnet.
4. The neodymium iron boron magnet as described in claim 2, characterized in that, The second structure accounts for 25.0%, 26.0%, 30.0% or 37.0% of the volume of the neodymium iron boron magnet.
5. The neodymium iron boron magnet as described in claim 2, characterized in that, The third structure accounts for 6.0% or 8.0% of the volume of the neodymium iron boron magnet.
6. The neodymium iron boron magnet as described in claim 2, characterized in that, The neodymium iron boron magnet comprises 58.0% of a first structure, 37.0% of a second structure, and 5.0% of a third structure; Alternatively, the neodymium iron boron magnet comprises 70.0% of a first structure, 25.0% of a second structure, and 5.0% of a third structure; Alternatively, the neodymium iron boron magnet comprises 68.0% of a first structure, 26.0% of a second structure, and 6.0% of a third structure; Alternatively, the neodymium iron boron magnet comprises 62.0% of a first structure, 30.0% of a second structure, and 8.0% of a third structure.
7. The neodymium iron boron magnet as described in claim 2, characterized in that, The Nd2Fe 14 The grain width of the B main phase is less than 500 nm.
8. The neodymium iron boron magnet as described in claim 7, characterized in that, The Nd2Fe 14 The grain width of the B main phase is less than 200 nm.
9. The neodymium iron boron magnet as described in claim 8, characterized in that, The Nd2Fe 14 The grain width of the B main phase is 43.7 nm, 75.5 nm, 115.0 nm or 151.0 nm.
10. The neodymium iron boron magnet as described in claim 2, characterized in that, The R'2Fe 14 The grain width of the B main phase is less than 500 nm.
11. The neodymium iron boron magnet as described in claim 10, characterized in that, The R'2Fe 14 The grain width of the B main phase is less than 200 nm.
12. The neodymium iron boron magnet as described in claim 11, characterized in that, The R'2Fe 14 The grain width of the B main phase is 43.7 nm, 75.5 nm, 115.0 nm or 151.0 nm.
13. The neodymium iron boron magnet as described in claim 1, characterized in that, The Nd content is 20.0%~26.0%; And / or, R' is Pr, and the content of Pr is 7.0%~10.0%; or, R' is Pr and Dy, wherein the content of Pr is 3.0%~7.0% and the content of Dy is 2.0%~4.0%; And / or, the content of Co is 1.5% to 3.5%; And / or, M is Ga, and the content of Ga is 0.1%~0.2%; or, M is Ga and Cu, wherein the content of Ga is 0.4%~0.5% and the content of Cu is 0.6%~0.7%; or, M is Ga and Al, wherein the content of Ga is 0.2%~0.35% and the content of Al is 0.01%~0.1%; And / or, the content of B is 0.85%~0.92%; And / or, the Fe content is 62.0%~66.0%.
14. The neodymium iron boron magnet as described in claim 13, characterized in that, The Nd content is 20.65%, 24.0%, 24.8%, or 25.5%.
15. The neodymium iron boron magnet as described in claim 13, characterized in that, R' is Pr, and the content of Pr is 7.15% or 9.59%; or, R' is Pr and Dy, wherein the content of Pr is 3.36% or 6.49%, and the content of Dy is 2.92% or 3.08%.
16. The neodymium iron boron magnet as described in claim 13, characterized in that, The content of Co is 1.7%, 2.4%, 3.0% or 3.5%.
17. The neodymium iron boron magnet as described in claim 13, characterized in that, M is Ga, and the content of Ga is 0.18%; or, M is Ga and Cu, wherein the content of Ga is 0.43% and the content of Cu is 0.64%; or, M is Ga and Al, wherein the content of Ga is 0.23% or 0.32% and the content of Al is 0.07% or 0.08%.
18. The neodymium iron boron magnet as described in claim 13, characterized in that, The content of B is 0.85%, 0.89%, 0.9% or 0.92%.
19. The neodymium iron boron magnet as described in claim 13, characterized in that, The Fe content is 62.39%, 64.37%, 64.44%, or 65.16%.
20. The neodymium iron boron magnet as described in claim 13, characterized in that, The neodymium iron boron magnet comprises the following components: Nd 20.65%, Pr 9.59%, Co 3.50%, Ga 0.18%, B 0.92%, and Fe 65.16%; Alternatively, the neodymium iron boron magnet comprises the following components: Nd 25.5%, Pr 3.36%, Dy 3.08%, Co 1.70%, Ga 0.43%, Cu 0.64%, B 0.85%, and Fe 64.44%; Alternatively, the neodymium iron boron magnet may comprise the following components: Nd 24.8%, Pr 7.15%, Co 2.4%, Ga 0.32%, Al 0.07%, B 0.89%, and Fe 64.37%.
21. A method for preparing a neodymium iron boron magnet as described in any one of claims 1 to 20, comprising the following steps: S1. First, second, and third thin strips are prepared respectively; wherein... The first thin strip is obtained by melting and rapid quenching the raw material of the first thin strip; the raw material of the first thin strip includes Nd 29.5%~32.0%, Co 1.0%~5.0%, M 0.1%~0.6%, B 0.86%~0.96%, and the balance is Fe; wherein, M is Ga; the percentages are the mass percentages of the raw material of the first thin strip; The second thin strip is obtained by melting and rapid quenching the raw material of the second thin strip; the raw material of the second thin strip includes R' 27.0%~30.0%, B 0.86%~0.96%, and the balance is Fe; wherein, R' is one or more of Pr, Dy and Tb; the percentage is the mass percentage of the raw material of the second thin strip; The third thin strip is obtained by melting and rapid quenching the raw material of the third thin strip; the raw material of the third thin strip includes R' 80.0%~97.5% and M 2.5%~18%; wherein, R' is one or more of Pr, Dy and Tb; M is one or more of Al, Cu and Ga; the percentage is the mass percentage of the raw material of the third thin strip; S2. The powder mixture is then subjected to hot pressing and hot deformation in sequence; The powder mixture comprises 70.0% to 90.0% of the powder of the first thin strip, 9.0% to 30.0% of the powder of the second thin strip, and 0.5% to 5.0% of the powder of the third thin strip; the percentages are the mass percentages of the powder mixture, and the sum of the mass percentages of each component is 100%.
22. The method for preparing a neodymium iron boron magnet as described in claim 21, characterized in that, In step S1, the content of Ga in the raw material of the first thin strip is 0.3%, 0.4% or 0.5%.
23. The method for preparing a neodymium iron boron magnet as described in claim 21, characterized in that, In step S1, the raw materials of the first thin strip include 29.5% Nd, 5.0% Co, 0.1% Ga, 0.96% B, and 64.44% Fe; Alternatively, in step S1, the raw materials of the first thin strip include Nd 30.0%, Co 2.0%, Ga 0.5%, B 0.88%, and Fe 66.62%; Alternatively, in step S1, the raw materials of the first thin strip include Nd 31.0%, Co 3.0%, Ga 0.4%, B 0.9%, and Fe 64.7%.
24. The method for preparing a neodymium iron boron magnet as described in claim 21, characterized in that, In step S1, in the raw material of the second thin strip, R' is Pr, and the content of Pr is 29.0%, 29.5%, or 30.0%; Alternatively, in the raw material of the second thin strip, R' is Dy, and the content of Dy is 28.0%; And / or, in step S1, the raw material of the second thin strip further includes Co, and the content of Co is 1.0% to 5.0%.
25. The method for preparing a neodymium iron boron magnet as described in claim 24, characterized in that, In step S1, the raw material of the second thin strip includes 30.0% Pr, 0.86% B, and 69.14% Fe; or, in step S1, the raw material of the second thin strip includes 29.0% Pr, 0.94% B, and 70.06% Fe; or, in step S1, the raw material of the second thin strip includes 29.5% Pr, 0.94% B, and 69.56% Fe.
26. The method for preparing a neodymium iron boron magnet as described in claim 24, characterized in that, In step S1, the raw materials of the second thin strip include Dy 28.0%, B 0.96%, and Fe 71.04%.
27. The method for preparing a neodymium iron boron magnet as described in claim 21, characterized in that, In step S1, in the raw material of the third thin strip, R' is Pr, and the content of Pr is 89.0%, 84.0%, or 96.5%; or, in step S1, in the raw material of the third thin strip, R' is Dy, and the content of Dy is 97.2%. And / or, in step S1, in the raw material of the third thin strip, M is Ga, and the content of Ga is 4.0%~12.0%; or, in step S1, in the raw material of the third thin strip, M is Cu, and the content of Cu is 14.0%~17.0%; or, in step S1, in the raw material of the third thin strip, M is Al, and the content of Al is 2.5%~3.5%.
28. The method for preparing a neodymium iron boron magnet as described in claim 27, characterized in that, In step S1, in the raw material of the third thin strip, M is Ga and the content of Ga is 11.0%; or, in step S1, in the raw material of the third thin strip, M is Cu and the content of Cu is 16.0%; or, in step S1, in the raw material of the third thin strip, M is Al and the content of Al is 2.8%.
29. The method for preparing a neodymium iron boron magnet as described in claim 27, characterized in that, In step S1, the raw materials of the third thin strip include 89.0% Pr and 11.0% Ga; Alternatively, in step S1, the raw material of the third thin strip includes 84.0% Pr and 16.0% Cu; Alternatively, in step S1, the raw material of the third thin strip includes 96.5% Pr and 3.5% Al; Alternatively, in step S1, the raw materials of the third thin strip include 97.2% Dy and 2.8% Al.
30. The method for preparing a neodymium iron boron magnet as described in claim 21, characterized in that, In step S1, the smelting includes: repeatedly smelting in an electric arc furnace under an inert gas protective atmosphere; And / or, in step S1, the rapid quenching includes: performing rapid quenching treatment in a vacuum rapid quenching furnace under an inert gas protective atmosphere, wherein the rotation speed of the cooling roller is 25 m / s; the inert gas is Ar gas.
31. The method for preparing a neodymium iron boron magnet as described in claim 21, characterized in that, In step S2, the powder mixture comprises 70.0% of the powder of the first thin strip, 29.0% of the powder of the second thin strip, and 1.0% of the powder of the third thin strip; Alternatively, in step S2, the powder mixture comprises 85.0% of the powder of the first thin strip, 11.0% of the powder of the second thin strip, and 4.0% of the powder of the third thin strip; Alternatively, in step S2, the powder mixture comprises 80.0% of the powder of the first thin strip, 18.0% of the powder of the second thin strip, and 2.0% of the powder of the third thin strip; Alternatively, in step S2, the powder mixture comprises 75.0% of the powder of the first thin strip, 22.0% of the powder of the second thin strip, and 3.0% of the powder of the third thin strip.
32. The method for preparing a neodymium iron boron magnet as described in claim 21, characterized in that, In step S2, the method for preparing the powder mixture includes: pulverizing the first thin strip, the second thin strip, and the third thin strip respectively to obtain powders of the first thin strip, the second thin strip, and the third thin strip; then mixing the powders of the first thin strip, the second thin strip, and the third thin strip; or, the method for preparing the powder mixture includes: pulverizing the first thin strip, the second thin strip, and the third thin strip together to obtain the powder mixture. And / or, the particle size D50 of the powder in the first thin strip, the powder in the second thin strip, and the powder in the third thin strip are each independently 150~250μm; And / or, in step S2, the temperature of the hot pressing is 500~650℃; And / or, in step S2, the hot pressing time is 1~5 min; And / or, in step S2, the pressure of the hot pressing is 50~200MPa; And / or, in step S2, the temperature of the heat deformation is 750-900℃; And / or, in step S2, the time for the thermal deformation is 1~5 min; And / or, in step S2, the pressure of the heat deformation is 100~300MPa; And / or, in step S2, the deformation rate of the thermal deformation is 50%~90%.
33. The method for preparing a neodymium iron boron magnet as described in claim 32, characterized in that, In step S2, the hot pressing time is 2 minutes.
34. The method for preparing a neodymium iron boron magnet as described in claim 32, characterized in that, In step S2, the pressure of the hot pressing is 150 MPa.
35. The method for preparing a neodymium iron boron magnet as described in claim 32, characterized in that, In step S2, the temperature of the heat deformation is 840°C.
36. The method for preparing a neodymium iron boron magnet as described in claim 32, characterized in that, In step S2, the thermal deformation time is 3 minutes.
37. The method for preparing a neodymium iron boron magnet as described in claim 32, characterized in that, In step S2, the pressure of the thermal deformation is 270 MPa.
38. The method for preparing a neodymium iron boron magnet as described in claim 32, characterized in that, In step S2, the deformation rate of the thermal deformation is 70%.
Citation Information
Patent Citations
A processing method for sintering neodymium-iron-boron magnetic material
CN101266858A
Rare earth permanent magnetic alloy and magnetic phase composite preparation method thereof
CN103187133A